Energy metabolism of growing blue foxes (Alopex lagopus) - Koskinen, Nita; Sepponen, Juhani; Rekilä, Teppo; Tauson, Anne-Helene (ru, 2009)
The blue fox (Alopex lagopus) is presently the most important species in fur farming in Finland. In recent years selective breeding programmes have focused on producing large and heavy animals. Ten years ago the average weight at pelting of blue fox vixens varied between 7 and 10 kg. Nowadays individuals weighing over 20 kg can be found. At present blue foxes are fed ad libitum during the growing - furring period. The blue fox exhibits seasonal fluctuations in feed intake and accretion of body fat, feed intake and body fat retention being very high during autumn and early winter if given free access to feed. Unrestricted feeding hence often leads to animals being very fat or even obese at the time of pelting. The accumulation of body fat may have dual purposes, both of crucial importance for animals living in the wild: first to provide insulation of the body and protection from excessive heat loss when ambient temperature is very low and second, to serve as an energy reserve in situations of scarcity. The main objective of this project was to establish baseline data on the energy requirement of growing blue foxes, by measuring feed intake, energy expenditure, and protein and fat retention. This project is based on the main hypothesis that the energy requirement of the blue fox is strongly regulated by photoperiod, and that voluntary feed intake and energy expenditure reflect seasonal changes. Animals, diet and treatment groups: Sixteen juvenile blue fox vixens were used. All animals were fed the same conventional fox diet. The average chemical composition of the diet was 37.8 % dry matter, 1.9 % ash, 11.7 % crude protein, 8.7 % fat and 15.5 % carbohydrate as fed. The feed for the experiment was produced as one batch and stored frozen until use. The animals were allocated to four different treatment groups and given different energy supply: (1) ad libitum, target body condition "very high"; (2) 20 - 30 % below the ad libitum group, target body condition "high"; (3) 35 - 45 % below ad libitum, target condition ...